Peran Preferensi Memediasi Pengaruh Revitalisasi Produk Wisata terhadap Keputusan Berkunjung Objek Wisata Danau Sipin Jambi - Mohammad Ihsan; Ade Perdana Siregar (Universitas Batanghari Jambi, 2020)
The world of tourism is something that has an important influence on the development and development of a country. The development of tourism will not be separated from physical and non-physical elements. Physical and non-physical elements will be considered in relation to the carrying capacity of objects and consideration of the impacts arising from tourism development. Tourism development must be based on planning, development and management direction. Local governments have an important role in tourism development. Lake Sipin is a lake located in the middle of the city of Jambi. Lake Sipin will definitely be very interesting, if it is packaged in such a way. The purpose of this study is to identify the effect of tourism product revitalization on preferences, identify the effect of tourism product revitalization and preferences on visiting decisions and identify preferences able to mediate the effect of tourism product revitalization on visiting decisions The population of this study is the Jambi city community while the sample is the Jambi city community which more than once visited the attractions of Lake Sipin Jambi as many as 150 people. The data method uses path analysis. The results of the study note that the revitalization of tourism products has a significant influence on the preferences of visitors to the Lake Sipin Jambi tourist attraction, the revitalization of tourism products and visitor preferences have a significant influence on the decision to visit the Lake Sipin Jambi tourist attraction and the visitor's preferences are able to mediate the effect of tourism product revitalization on the decision visited the attractions of Lake Sipin Jambi